2015
DOI: 10.1155/2015/951704
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Action Potential Alternans in Rabbit Heart during Acute Regional Ischemia

Abstract: This study investigates the development of the spatiotemporal pattern of action potential alternans during acute regional ischemia. Experiments were carried out in isolated Langendorff-perfused rabbit heart using a combination of optical mapping and microelectrode recordings. The alternans pattern significantly changed over time and had a biphasic character reaching maximum at 6–9 min after occlusion. Phase I (3–11 minutes of ischemia) is characterized by rapid increase in the alternans magnitude and expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 28 publications
7
12
0
Order By: Relevance
“…Previous study supports that the depolarization alternans is linked to conduction abnormalities in the ischemia region [22]. The conduction block occurs under hyperkalemic conditions.…”
Section: Discussionsupporting
confidence: 58%
“…Previous study supports that the depolarization alternans is linked to conduction abnormalities in the ischemia region [22]. The conduction block occurs under hyperkalemic conditions.…”
Section: Discussionsupporting
confidence: 58%
“…; Martišienė et al . ). During acute myocardial ischaemia, a premature ventricular contraction (PVC), the compensatory pause following such a PVC, or an intentional pause in stimulation can initiate a phase of alternans or make alternans cease (Hellerstein & Liebow, ; Kataoka & Yoshimura, , Dilly & Lab, ).…”
Section: Photograph Of the Organisers Of The Mines Centennial Symposiummentioning
confidence: 97%
“…; Martišienė et al . ). Concordant alternans, and more so discordant alternans, presages the transition to malignant ventricular arrhythmias such as ventricular tachycardia and fibrillation (Downar et al .…”
Section: Photograph Of the Organisers Of The Mines Centennial Symposiummentioning
confidence: 97%
See 1 more Smart Citation
“…The numerical model showed that when paced in tissue at fast cycle lengths, it produces APA alternans in a single cell and resulted in conduction block in space. Recently Myles, et al [22] have shown that cellular alternans of action potential amplitude is notably present in rabbit hearts with heart failure and that APA is of particular importance in the initiation of VF, and in fact more important than APD alternans [22,33]. They showed that post-infarction hearts are more vulnerable to ventricular arrhythmias at rapid rates and that APA alternans were associated with conduction block and VF.…”
mentioning
confidence: 99%